Synthesis, radiolabeling, and evaluation of a (4-quinolinoyl)glycyl-2-cyanopyrrolidine analogue for fibroblast activation protein (FAP) PET imaging - Zhang, Ni; Pan, Fei; Pan, Lili; Diao, Wei; Su, Feijing; Huang, Rui; Yang, Bo; Li, Yunchun; Qi, Zhongzhi; Zhang, Wenjie; Wu, Xiaoai (Frontiers in Bioengineering and Biotechnology, 2023)
Fibroblast activation protein (FAP) is regarded as a promising target for the diagnosis and treatment of tumors as it was overexpressed in cancer-associated fibroblasts. FAP inhibitors bearing a quinoline scaffold have been proven to show high affinity against FAP in vitro and in vivo, and the scaffold has been radio-labeled for the imaging and treatment of FAP-positive tumors. However, currently available FAP imaging agents both contain chelator groups to enable radio-metal labeling, making those tracers more hydrophilic and not suitable for the imaging of lesions in the brain. Herein, we report the synthesis, radio-labeling, and evaluation of a 18F-labeled quinoline analogue ([18F]3) as a potential FAP-targeted PET tracer, which holds the potential to be blood–brain barrier-permeable. [18F]3 was obtained by one-step radio-synthesis via a copper-mediated SNAR reaction from a corresponding boronic ester precursor. [18F]3 showed moderate lipophilicity with a log D7.4 value of 1.11. In cell experiments, [18F]3 showed selective accumulation in A549-FAP and U87 cell lines and can be effectively blocked by the pre-treatment of a cold reference standard. Biodistribution studies indicated that [18F]3 was mainly excreted by hepatic clearance and urinary excretion, and it may be due to its moderate lipophilicity. In vivo PET imaging studies indicated [18F]3 showed selective accumulation in FAP-positive tumors, and specific binding was confirmed by blocking studies. However, low brain uptake was observed in biodistribution and PET imaging studies. Although our preliminary data indicated that [18F]3 holds the potential to be developed as a blood–brain barrier penetrable FAP-targeted PET tracer, its low brain uptake limits its application in the detection of brain lesions. Herein, we report the synthesis and evaluation of [18F]3 as a novel small-molecule FAPI-targeted PET tracer, and our results suggest further structural optimizations would be needed to develop a BBB-permeable PET tracer with this scaffold.